已知f(1+2x)=x-4x-1,求f(3-4x)

来源:学生作业帮助网 编辑:作业帮 时间:2024/08/26 04:37:53
已知f(1+2x)=x-4x-1,求f(3-4x)
xݔkPQD!*uk\""PEP؋)ڡst{ڿḾ-v|s\I7MGg>j|2;S?+*]$z'?>U*A-+eݪ#`gRi!UKץQ98on8KFmhV<=Ͼ}:x8x39ٛr MN;oomցuxyRZc ǹ@QHQ{/(z]xn JvB5gX# 8>5B8d[Ѣ߽8 caNM"\?qr^Lǖܴ5O E%%2

已知f(1+2x)=x-4x-1,求f(3-4x)
已知f(1+2x)=x-4x-1,求f(3-4x)

已知f(1+2x)=x-4x-1,求f(3-4x)
令a=1+2x
x=(a-1)/2
f(a)=[(a-1)/2]^2-4(a-1)/2-1
f(3-4x)=[(3-4x-1)/2]^2-4(3-4x-1)/2-1
=(1-2x)^2-2(2-4x)-1
=4x^2-4x+1-4+8x-1
=4x^2+4x-4
请采纳答案,支持我一下.

收起

令a=1+2x
x=(a-1)/2
f(a)=[(a-1)/2]^2-4(a-1)/2-1
f(3-4x)=[(3-4x-1)/2]^2-4(3-4x-1)/2-1
=(1-2x)^2-2(2-4x)-1
=4x^2-4x+1-4+8x-1
=4x^2+4x-4

令t=1+2x,x=(t-1)/2,
f(t)=-3*(t-1)/2-1,
f(3-4x)
=-3*(3-4x-1)/2-1
=6x-4

收起